Evaluasi Kinerja Bagian Protokol Pemerintah Provinsi Sumatera Selatan - Fahtiaz, Anatasya Nur; Hakim, Arif Rahman; Zuber, Konar (@-Publik: Jurnal Administrasi Publik, 2026)
The purpose of this study is to evaluate the performance of the Protocol Section of the South Sumatra Provincial Government. The problem of employee performance in the Protocol Section of the South Sumatra Provincial Government is not optimal and the employee performance appraisal process is often subjective and can be influenced by the preferences or personal views of superiors or evaluators. This research method uses a qualitative research approach. Data or information is collected through interviews with informants, observation and documentation. The results of the study show that: Context: the limited number of employees handling various protocol activities causes overlapping in the division of tasks. This makes the workload feel heavy and uneven among employees. In addition, the lack of employee understanding of each other's duties and functions, coupled with minimal work experience and employee rotation within the work unit, also exacerbates the situation. Input: Although facilities and infrastructure are adequate, there are several things that need to be improved, especially additional equipment such as printers, scanners, photocopiers, and other office equipment needed to support administrative tasks. Promotional tools such as presentation materials, such as banners, posters, brochures, and other promotional materials to promote events or activities organized by the provincial government, are also needed. Process: The employee performance appraisal process is often subjective and can be influenced by the preferences or personal views of superiors or evaluators. However, the South Sumatra Provincial Protocol Section conducts performance evaluations by assessing the Protocol Section's performance in meeting service standards and compliance with established protocols, then identifying strengths and weaknesses in the implementation of protocol tasks, and then providing recommendations for improvement and performance enhancement. Product: Effective performance results in the protocol section not only provide direct benefits in organizing official events but also have a broader impact in strengthening the organization's image, maintaining good relationships, and increasing public trust.